Researching medical education - Cleland, Jennifer A.; Durning, Steven J. (Chichester, West Sussex ; Hoboken,NJ : John Wiley & Sons, Ltd., 2015)
"Researching Medical Education is an authoritative guide to excellence in educational research in the health professions. Presented by the Association for the Study of Medical Education and the Association for Medical Education in Europe, Researching Medical Education includes contributions from a team of international clinicians and non-clinical researchers in health education, representing a range of disciplines and backgrounds. This accessible reference provides readers with the basic building blocks of research, introduces a range of theories and how to use them, illustrates a diversity of methods and their use, and gives guidance on practical researcher development. By linking theory and design and methods across the health profession education research spectrum, this book supports the improvement of quality, capacity building and knowledge generation. Researching Medical Education is the ideal resource for anyone researching health education, from undergraduate, through postgraduate training, to continuing professional development"--Publisher's description.
What are values and how can we assess them? implications for values-based recruitment in healthcare / Fiona Patterson, Máire Kerrin, Marise Ph. Born, Janneke K. Oostrom, and Linda Prescott-Clements -- Emotions and learning : cognitive theoretical and methodological approaches to studying the influence of emotions on learning / Meghan McConnell and Kevin Eva -- Research on instructional design in the health sciences : from taxonomies of learning to whole-task models / Jeroen J.G. van Merrienboer and Diana HJM Dolmans -- Cognitive load theory : researching and planning teaching to maximize learning / Jimmie Leppink, Tamara van Gog, Fred Paas, and John Sweller -- Deliberate practice and mastery learning origins of expert medical performance / William C. McGaghie and Theresa Kristopaitis -- Reframing research on widening participation in medical education : using theory to inform practice / Sandra Nicholson and Jennifer Cleland -- Qualitative research methodologies : embracing methodological borrowing, shifting, and importing / Lara Varpio, Maria Athina Martimianakis, and Maria Mylopoulos -- How to tell compelling scientific stories : tips for artful use of the research manuscript and presentation genres / Lorelei Lingard and Erik Driessen -- Leadership, management, and mentoring : applying theory to practice / Judy McKimm and Helen O'Sullivan -- Programmatic research : building and sustaining capacity / Trevor Gibbs and David Taylor.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Education, Medical; Biomedical Research; Education, Dental; Education, Nursing; Learning; Research Design; Medical education; Learning; HEALTH & FITNESS / Holism; HEALTH & FITNESS / Reference; MEDICAL / Alternative Medicine; MEDICAL / Atlases; MEDICAL / Essays; MEDICAL / Family & General Practice; MEDICAL / Holistic Medicine; MEDICAL / Osteopathy; Education, Dental; Education, Medical; Education, Nursing; Education; Learning; Learning; Medical education; Electronic books; Electronic books